The effect of gender and physical attractiveness on personal space. - Clement, Edgar M.
This study was conducted to determine if gender and physical attractiveness had an effect on personal space. Personal space was operationally defined as the distance between the subject and the confederate, after the confederate invaded the subjects' personal space in a waiting room setting. Twenty-eight female college students participated in the study . They were exposed to four treatment conditions that included the following: physically attractive male, physically attractive female, physically unattractive male and phyisically unattractive female. The design of the study was 2 X 2 Within-Subject Factorial Design. Datan were analyzed using a 2 X 2 Within-Subject Analysis of Variance Test. Results showed that gender had an effect on personal space, while physical attractiveness had none. Moreover, there was no interaction effect between gender and physical attractiveness